2021
DOI: 10.1136/bmj.n287
|View full text |Cite|
|
Sign up to set email alerts
|

Covid-19: How the UK is using lateral flow tests in the pandemic

Abstract: Lateral flow tests are pivotal to the UK government’s strategy to reduce the spread of the coronavirus by identifying asymptomatic patients. But with questions over their accuracy, Ingrid Torjesen asks whether they are being used appropriately

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 3 publications
0
51
0
Order By: Relevance
“…Finally, we assume that the tests being used are Lateral Flow Devices, LFD, which are assigned to have a false positive probability, P fp and a false negative probability of P fn . Throughout the simulations, we will vary P fn but keep the false positive probability fixed to P fp = 0.003, in agreement with existing LFD studies [19, 22, 36].…”
Section: Computational Frameworkmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, we assume that the tests being used are Lateral Flow Devices, LFD, which are assigned to have a false positive probability, P fp and a false negative probability of P fn . Throughout the simulations, we will vary P fn but keep the false positive probability fixed to P fp = 0.003, in agreement with existing LFD studies [19, 22, 36].…”
Section: Computational Frameworkmentioning
confidence: 97%
“…In the UK, there is currently a focus on using Lateral Flow Devices (LFDs) as a means of detecting infected individuals to better manage infection [16, 17, 18]. Controversially, it has been suggested that a negative result from an LFD might be used to release people who, following a close contact with an infected individual, had been advised to self-isolate [19, 20, 21]. Critically, LFDs have a high false negative rate [22], thus we investigated how beneficial they would be in relation to other NPIs, particularly in a landscape of vaccine rollout where personal adherence with contact and isolation policies may be in decline [23].…”
Section: Introductionmentioning
confidence: 99%
“…Lateral flow tests (LFTs) are not as sensitive as PCR tests at picking up positive cases, but they are relatively cheap, provide results in less than 30 minutes, and are capable of identifying those with the highest viral loads, who are considered to be the most infectious 1. School testing uses the Innova test, although the Department of Health and Social Care says that other brands might be used in the future.…”
Section: How Is Testing Being Implemented In Secondary Schools?mentioning
confidence: 99%
“…Students are tested under supervised conditions with rapid lateral flow devices, which do not require laboratory processing, such as the Innova tests, which the UK government has spent over £1.3bn on purchasing 1…”
Section: Costly Moonshotmentioning
confidence: 99%